Low Nitric Oxide Bioavailability Increases Renin Production in the Collecting Duct - Curnow, Andrew C.; Gonsalez, Sabrina R.; Gogulamudi, Venkateswara R.; Visniauskas, Bruna; Simon, Eric E.; Gonzalez, Alexis A.; Majid, Dewan S. A.; Lara, Lucienne S.; Prieto, Minolfa C. (Frontiers in Physiology, 2020)
In the kidney, the stimulation of renin production by the collecting duct (CD-renin) contributes to the development of hypertension. The CD is a major nephron segment for the synthesis of nitric oxide (NO), and low NO bioavailability in the renal medulla is associated with hypertension. However, it is unknown whether NO regulates renin production in the CD. To test the hypothesis that low intrarenal NO levels stimulate the production of CD-renin, we first examined renin expression in the distal nephron segments of CD-eNOS deficient mice. In these mice, specific CD-renin immunoreactivity was increased compared to wild-type littermates; however, juxtaglomerular (JG) renin was not altered. To further assess the intracellular mechanisms involved, we then treated M-1 cells with either 1 mM L-NAME (L-arginine analogue), an inhibitor of NO synthase activity, or 1 mM NONOate, a NO donor. Both treatments increased intracellular renin protein levels in M-1 cells. However, only the inhibition of NOS with L-NAME stimulated renin synthesis and secretion as reflected by the increase in Ren1C transcript and renin protein levels in the extracellular media, respectively. In addition, NONOate induced a fast mobilization of cGMP and intracellular renin accumulation. These response was partially prevented by guanylyl cyclase inhibition with ODQ (1H-(1,2,4) oxadiazolo[4,3-a]quinoxalin-1]. Accumulation of intracellular renin was blocked by protein kinase G (PKG) and protein kinase C (PKC) inhibitors. Our data indicate that low NO bioavailability increases CD-renin synthesis and secretion, which may contribute to the activation of intrarenal renin angiotensin system.